2018
DOI: 10.1155/2018/4020492
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Agonists and Cardiovascular Disease in Patients with Type 2 Diabetes

Abstract: Diabetes mellitus is a chronic disease prevalence of which is high and continually growing. Cardiovascular disease continues to be the leading cause of death in patients with T2DM. The prevention of cardiovascular complications and the cardiovascular safety of treatments should be a primary objective when selecting treatment. Among all the drugs available, the compounds known as glucagon-like peptide-1 receptor agonists (GLP-1 RAs) appear to be not just innocuous in terms of CVD but indeed to be beneficial. GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 63 publications
0
74
0
3
Order By: Relevance
“…The mechanism by which GLP1 receptor agonists influence cardiovascular outcome is not well understood. These agents have weight‐reducing effects and cause a modest reduction in systolic blood pressure of about 2–3 mmHg, probably through natriuresis, improved endothelial function, and vasodilation . The blood pressure reduction is accompanied by an increase in heart rate, and whether this influences cardiovascular outcomes remains uncertain.…”
Section: Glucagon‐like Peptide 1 Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which GLP1 receptor agonists influence cardiovascular outcome is not well understood. These agents have weight‐reducing effects and cause a modest reduction in systolic blood pressure of about 2–3 mmHg, probably through natriuresis, improved endothelial function, and vasodilation . The blood pressure reduction is accompanied by an increase in heart rate, and whether this influences cardiovascular outcomes remains uncertain.…”
Section: Glucagon‐like Peptide 1 Receptor Agonistsmentioning
confidence: 99%
“…These agents have weight-reducing effects and cause a modest reduction in systolic blood pressure of about 2-3 mmHg, 34,35 probably through natriuresis, improved endothelial function, and vasodilation. 36,37 The blood pressure reduction is accompanied by an increase in heart rate, 38 and whether this influences cardiovascular outcomes remains uncertain. There is some evidence that GLP1 receptor agonists may modulate inflammation and have other beneficial effects for atherosclerosis and cardiovascular disease beyond their metabolic profile.…”
Section: Cardiovascular Outcome Trialsmentioning
confidence: 99%
“…Most studies investigating the impact on lipid profile were performed with either liraglutide or exenatide in healthy subjects and in patients with T2DM and showed significant reduction of fasting and postprandial chylomicron TG levels, modest decreases in TC and LDLc and small or no significant change in HDLc levels (195). In the case of liraglutide, it seems that there is direct effect of the drug on the expression of genes involved in the biosynthesis of chylomicron and a reduction of APOB48 pool (194,196).…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%
“…11 Recent studies have shown that GLP-1 agonists have pleiotropic effects that can modulate cardiovascular complications, such as increasing heart rate, reducing blood pressure, and improving myocardial infarction and vascular endothelial function. [12][13][14] Lixisenatide is an improved shortacting GLP-1 receptor agonist widely used in clinical practice. Lixisenatide was developed based on the structure of the earlier GLP-1 analog exendin-4.…”
Section: Introductionmentioning
confidence: 99%